Potential utilization of dairy industries by-products and wastes through microbial processes: A critical review - Sar, Taner; Harirchi, Sharareh; Ramezani, Mohaddaseh; Bulkan, Gulru; Akbas, Meltem Yesilcimen; Pandey, Ashok; Taherzadeh, Mohammad J. (Elsevier, 2022)
The dairy industry generates excessive amounts of waste and by-products while it gives a wide range of dairy products. Alternative biotechnological uses of these wastes need to be determined to aerobic and anaerobic treatment systems due to their high chemical oxygen demand (COD) levels and rich nutrient (lactose, protein and fat) contents. This work presents a critical review on the fermentation-engineering aspects based on defining the effective use of dairy effluents in the production of various microbial products such as biofuel, enzyme, organic acid, polymer, biomass production, etc. In addition to microbial processes, techno-economic analyses to the integration of some microbial products into the biorefinery and feasibility of the related processes have been presented. Overall, the inclusion of dairy wastes into the designed microbial processes seems also promising for commercial approaches. Especially the digestion of dairy wastes with cow manure and/or different substrates will provide a positive net present value (NPV) and a payback period (PBP) less than 10 years to the plant in terms of biogas production.
Keywords: Dairy eff luents; Microbial production; Bioconversion; Resource recovery; Techno-economic analysis